2012
DOI: 10.1016/j.diff.2012.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Lung endothelial cells strengthen, but brain endothelial cells weaken barrier properties of a human alveolar epithelium cell culture model

Abstract: The blood-air barrier in the lung consists of the alveolar epithelium, the underlying capillary endothelium, their basement membranes and the interstitial space between the cell layers. Little is known about the interactions between the alveolar and the blood compartment. The aim of the present study was to gain first insights into the possible interplay between these two neighboured cell layers. We established an in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 43 publications
3
31
0
Order By: Relevance
“…These results are consistent with previous studies that have found that A549 cells are incapable of forming functional tight junctions [18, 40, 50, 55]. The contrasting barrier functions between the two cell lines may be due to the differential expression of junctional proteins.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with previous studies that have found that A549 cells are incapable of forming functional tight junctions [18, 40, 50, 55]. The contrasting barrier functions between the two cell lines may be due to the differential expression of junctional proteins.…”
Section: Discussionsupporting
confidence: 93%
“…Reported culture conditions for air-liquid culture of NCI-H441 cells vary widely in seeding density (20,000–5,000,000 cells/cm 2 ) [23, 4043], dexamethasone concentration (10–2000 nM) [22, 27, 4042], and the use of supplements such as ITS and T3 [27, 28]. We examined the effect of these variables on the phenotypic and functional characteristics of the model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…102 The alveolar epithelium is made up of two epithelial cell types, namely, the terminally differentiated squamous alveolar epithelial type-1 (AT-I) and the surfactant-producing cuboidal alveolar epithelial type-II (AT-II) cells. 102 …”
Section: Pulmonary Modelsmentioning
confidence: 99%
“…Consequently, microvascular endothelial cells form tighter cell–cell junctions [105], [106]. Human lung microvascular endothelial cells may also enhance the barrier function of epithelial cells [107], which actually provide a barrier with a smaller transport threshold than that of the endothelium. Compared to the 5-nm cutoff for endothelial cell–cell barriers, the epithelium provides a barrier to molecules greater than 1 nm.…”
Section: Strategies For Cellular Repopulation: Cell Types and Usmentioning
confidence: 99%